Role of Endoplasmic Reticulum and Oxidative Stress Parameters in the Pathophysiology of Disease-Related Malnutrition in Leukocytes of an Outpatient Population - Celia Bañuls (Nutrients, 2019)
Cellular pathways such as inflammation or oxidative stress are the cause and triggers of disease-related malnutrition (DRM), but the influence of these markers on endoplasmic reticulum (ER) stress is unknown. The objective of this study was to analyze the relationship between mitochondrial function and ER stress parameters in a DRM population. The study population was composed of 82 outpatient subjects, of whom 45 were diagnosed with DRM and 37 were confirmed to be normonourished according to the American Society for Parenteral and Enteral Nutrition ASPEN criteria. We evaluated anthropometrical and biochemical parameters, pro-inflammatory cytokines in serum. Oxidative and ER stress markers were analyzed in leukocytes. DRM patients showed significant reductions in albumin and transferrin concerning the normonourished group, and also displayed higher levels of hsCRP, IL6, and TNFα, and the soluble adhesion molecules VCAM-1 and ICAM-1. Besides, oxygen consumption and mitochondrial membrane potential were reduced and Radical Oxygen Species ROS production was enhanced in DRM patients. In the case of ER markers, protein and mRNA expression revealed that CHOP, ATF6, and the P-eIF2α signal were enhanced in malnourished patients compared to control subjects. Correlation studies supported a relationship between weight loss and increased inflammation, mitochondrial dysfunction, and compromised function of the ER. Our results demonstrate that ER stress signaling pathways are influenced by inflammation and mitochondrial function in the leukocytes of a DRM population.